(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
The Canarian artist Josefina de la Torre (Las Palmas de Gran Canaria, 1907- Madrid, 2002) played the most diverse roles during her life: she was a poet, novelist, screenwriter, adaptor, dubbing artist, film, theater and television actress and even director of a fashion show. She had an extraordinary existence that extended throughout the 20th century. Aware of this, she wrote a series of diaries intermittently and several attempts at memoirs to reclaim her prominence in the cultural history of Spain. All these texts remain unpublished and their existence was unknown until now. In this paper we analyze the various diaries and unfinished memoirs written by the author to unravel their content and discover this secret writing through which she wanted to safeguard her experience and her identity.